Ancient Lesbian Wine, Similar to Modern Madeira? - Komar, Paulina (Polskie Towarzystwo Filologiczne, 2022)
When describing Lesbian wine, Pliny the Elder referred to it as “mare sapit” (HN XIV 74), a phrase that is usually associated with wines mixed with sea water, a process typical for some other Greek vintages, but certainly not Lesbian. By approaching the literary testimonies regarding ancient wine making from the perspective of contemporary oenology, I will attempt to show that Pliny experienced a taste similar to that of today’s Madeira wine.